Reforming Rural Russia : State, Local Society, and National Politics, 1855-1914. - Wcislo, Francis William (Studies of the Harriman Institute., 2014)
As he examines administrative reform of Russian rural local government between the abolition of serfdom and World War I, Francis William Wcislo takes as his theme the repeated attempts of tsarist statesmen to restructure the most critical mediating link between the autocratic state and a rapidly modernizing agrarian society. His broader objective, however, is to use the issue of autocratic politics to probe the character and evolution of bureaucratic mentalit in this period. Wcislo links the social, psychological, ideological, and institutional nexus of the bureaucracy with its social.